Justice for George Floyd and a reckoning for global mental health - Weine, Stevan (Glob Ment Health (Camb), 2020)
In the wake of George Floyd's killing by police in Minneapolis and the global response inspired by Black Lives Matter, it is time for the field of global mental health to reexamine how we have acknowledged and addressed racism in our institutions, our research, and our mental health services. In solidarity with street level responses, this is an important opportunity to understand and collaboratively respond to public demand for systemic change. To respond effectively, it is vital to (1) be aware of the colonial history that influences today's practices, and move forward with anti-colonial and anti-racist actions; (2) identify where and why diversity and representation are lacking in the global mental health workforce, then follow steps to combat these disparities; and (3) work with communities and institutions to end both police violence and structural violence.